Eksperimen Pembelajaran Matematika Dengan Pendekatan Saintifik Berbasis Concept Map Dan Mind Mapping Ditinjau Dari Komunikasi Matematis Kelas VIII SMP Negeri 1 Gatak, Sukoharjo Tahun 2015/2016 - Mulyadi, Tri, Dra. Nining Setyaningsih, M.Si (2017)
The purpose of this study to examine (1) the effect of the strategy the scientific is based Concept maps and the scientific is based Mind Mapping towards mathematics learning achievement of students, (2) the effect of level of ability to mathematical communication towards mathematics learning achievement of students, (3) the interaction between the learning strategies and the ability to mathematical communication towards mathematics learning achievement of students. Quantitative research with a quasi experimental design. The population of the research is all of student seventh grade atSMP Negeri 1 Gatak, Sukoharjo. The sampel of research is VIII f and VIII G graders. The data collection technique using the test methods, questionnaire and documentation. Data were analyzed using analysis of variance of two paths with different cell. The results of the study with α = 5% is (1) there is a significant relationship bet strategy the scientific is based Concept maps and the scientific is based Mind Mapping towards mathematics learning achievement of students i.e. F_A=4.657 >F_(0.05;1,60)=4.001; (2) the is significant influence mathematics learning achivement of student in terms of the ability of mathematical communication i.e. F_B=29,727 >F_(0.05;2,60)=3.150; and (3) there is no interaction between the learning strategies and the ability to mathematical communication learning achievement of students i.e. F_AB=1,640<F_(0.05;2,60)=3.150